A simulação clínica como estratégia de ensino de medidas de prevenção e controle de infecções relacionadas à assistência à saúde - Dias, Ana Angélica Lima (2019)
Aim: To assess the teaching process based on simulations as an educational strategy for the measures of prevention and control infections related to health assistance (IRAS). Method: The study was carried out in two stages: 1st Stage is a methodological study for the development and validation of content from two simulated clinical scenarios. The content analysis was carried out by the content validity index (CVI) in regards to the range, clarity and pertinence. The scenarios were forwarded through the Google forms® app link to simulation and IRAS specialists. 2nd Stage was a semi-experimental and cross-sectional study aimed at measuring the simulation results (knowledge, satisfaction, self-confidence), the simulation design, the educational practice and the debriefing experience processes. The data were analyzed using the descriptive statistic and the Generalized Estimating Equation Model-GEE. The study was carried out by nursing graduates of the 5th through the 9th terms of the Federal University of São João Del-rei - Centro-oeste campus. The data collection took place in two occasions: Day 1 - pre-testing (knowledge assessment test) and expositional class with dialogue; Day 2 - Participation in two clinical simulations and fulfilment of the Scale of Student Satisfaction and Self-Confidence in Learning (SSSL), of the Simulation Design Scale (SDS), of the Educational Practices Questionnaire (EPQ), and of the Debriefing Experience Scale (DES) and post-testing. Results: 1st Stage: The scenarios were developed based on the conceptual components of the National League for Nursing Jeffries Simulation Theory and the International Nursing Association for Clinical Simulation and a Learning Standards of Best Practices: Simulation. There were 10 experts in the validation process, and the CVI was ≥ 80%. 2nd Stage: There were 44 students and 28 (63,65) were in intermediate graduation (5th through the 7th terms), while 28 (63,6%) students actively participated in the scenario and 23 (52,3%) students had previous knowledge with simulations. There was no statistical difference in the number of correct answers in knowledge assessment instrument results in the pre-testing and post-testing. The SSSL showed an average of 4,5±0,3the average results of the Satisfaction domain were superior to the average results of the Self-confidence domain. The SDS showed an average of 4,7±0,2. The SDS showed an average of 4,7±0,2 where the items scoring the lowest were the ones that assessed realism. The SDS items that scored the least were the ones that assessed realism. The EPQ showed an average of 4,7+0,2. The DES showed an average of 4,8+0,2The instrument reliability was high (>0,81%).The learners' average score in all the instruments were higher for the ones who had previously participated of a simulation, there was no difference in their average score regarding their participation condition (active or observer) and the final graduation period students (8th and 9th terms) scored higher in average for the DES. Conclusion: Simulation-based teaching is an appropriate educational strategy for teaching IRAS prevention and control measures to nursing undergraduates.